2004
DOI: 10.1128/aem.70.4.2230-2239.2004
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Archaeal Diversity Reveals an Abundance of HalophilicArchaeain a Low-Salt, Sulfide- and Sulfur-Rich Spring

Abstract: The archaeal community in a sulfide-and sulfur-rich spring with a stream water salinity of 0.7 to 1.0% in southwestern Oklahoma was studied by cloning and sequencing of 16S rRNA genes. Two clone libraries were constructed from sediments obtained at the hydrocarbon-exposed source of the spring and the microbial mats underlying the water flowing from the spring source. Analysis of 113 clones from the source library and 65 clones from the mat library revealed that the majority of clones belonged to the kingdom Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 65 publications
2
91
0
2
Order By: Relevance
“…Can these organisms use elemental sulfur, which may be very abundant, as the alternative terminal electron acceptor? This question was addressed several times in the past 30 years (Grant and Ross, 1986;Tindall and Trüper, 1986;Elshahed et al, 2004aElshahed et al, , 2004b, but no conclusive answer has been found. Acetate is an abundant electron donor and carbon source in anoxic habitats, which accumulates in the absence of high-potential electron acceptors, such as nitrate or ferric ion (Afshar et al, 1998;Kashevi et al, 2002;Slobodkina et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Can these organisms use elemental sulfur, which may be very abundant, as the alternative terminal electron acceptor? This question was addressed several times in the past 30 years (Grant and Ross, 1986;Tindall and Trüper, 1986;Elshahed et al, 2004aElshahed et al, , 2004b, but no conclusive answer has been found. Acetate is an abundant electron donor and carbon source in anoxic habitats, which accumulates in the absence of high-potential electron acceptors, such as nitrate or ferric ion (Afshar et al, 1998;Kashevi et al, 2002;Slobodkina et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Teniendo en cuenta que los microorganismos halófilos de los dominios Archaea y Bacteria tienen un amplio espectro metabólico, se utilizaron diferentes sustratos orgánicos comúnmente reportados como materia orgánica disuelta en sistemas acuáticos proveniente del medio ambiente circundante o de fuentes autóctonas como el fitoplancton, bacteriopláncton y perifiton, ya sea por la producción de exopolisacáridos, la muerte celular o la liberación de exudados (Gremm & Kaplan, 1997). Además, a algunas series se les agregó un suplemento de antibióticos para favorecer el aislamiento de organismos del dominio Archaea como se ha descrito anteriormente (Elshahed, et al, 2004). Después de la esterilización, los MB-AER fueron suplementados con 0,2 g/L de extracto de levadura (Sigma) y con diferentes fuentes de carbono como ácidos orgánicos, alcoholes, azúcares, aminoácidos, polisacáridos y lípidos (Díaz-Cárdenas, 2011).…”
Section: Generación De Inventarios Biológicos a Partir Del Aislamientunclassified
“…For example, while most halophilic archaea exhibit optimal growth at near neutral pH, many are alkaliphilic and require at least pH 8.5 for growth . Recent molecular studies have revealed the presence of halophilic archaea in several low salinity environments (Elshahed et al, 2004). In addition, Purdy and colleagues (2004) isolated haloarchaea from a coastal salt marsh that exhibited optimal growth at 10% (1.7 M) NaCl but could grow slowly at 2.5% (0.43 M) NaCl.…”
Section: Halophilic Archaeamentioning
confidence: 99%
“…The numbers of genera is reached to 35 (November 2011-Euzebylist) and Salarchaeaum is the last added extremely halophilic genus (Shimane et al, 2011). Most species of Halobacteriaceae are true extreme halophiles according to Kushner's definition (Kushner, 1978), however, Halobacteriaceae contains some species which can grow in low salinity for instance, Haloferax sulfurifontis (Elshahed et al, 2004), Haladaptatus paucihalophilus "the spesific epithet refers to low salt loving", (Savage et al, 2007) and Halosarcina pallida (Savage et al, 2008). Diverse 16S rRNA gene sequences related to haloarchaea were recovered from tidal marine and salt marsh sediments, suggesting the existence of haloarchaea capable of growth at lower salt levels.…”
Section: Wwwintechopencommentioning
confidence: 99%